Multifrequency study of HH 137 and HH 138: Discovering new knots and molecular outflows with Gemini and APEX - Ferrero, Leticia Virginia (2020)
We present a multiwavelength study of two Herbig-Haro (HH) objects (137 and 138) that may be associated. We use Gemini H2 (2.12 μm) and K (2.2 μm) images, as well as Atacama Pathfinder EXperiment molecular line observations and Spitzer image archives. Several H2 knots, linked to the optical chain of knots of HH 137, are identified in the Gemini and Spitzer 4.5 μm images. New shock excited regions related to the optical knots delineating HH 138 are also reported. In addition, a bright 4.5 μm 0.09pc-long arc-shaped structure, roughly located mid-way between HH 137 and HH 138, is found to be associated with two Spitzer Class I/II objects, which are likely to be the exciting stars. These sources are almost coincident with a high-density molecular clump detected in 12CO(3 — 2), 13CO(3 — 2), C18O(3 — 2), HCO+(3 — 2), and HCN(3 — 2) molecular lines with an local thermodynamic equilibrium (LTE) mass of 36 M0. The 12CO(3 — 2) emission distribution over the observed region reveals molecular material underlying three molecular outflows. Two of them (outflows 1 and 2) are linked to all optical knots of HH 137 and HH 138 and to the H2 and 4.5 μm shock emission knots. In fact, the outflow 2 shows an elongated 12CO blue lobe that coincides with all the H2 knots of HH 137, which end at a terminal H2 bow shock. We propose a simple scenario that connects the outflows to the dust clumps detected in the region. A third possible outflow is located to the north-east projected towards a secondary weak and cold dust clump.